Ulangan 31-34 Sebagai Teks Reflektif untuk Mengantisipasi Post Power Syndrome bagi Pemimpin Kristen - Hasibuan, Serepina (STT Internasional Harvest Tangerang, 2024)
One of the common challenges faced by long-serving leaders, particularly those who are advanced in age, is post-power syndrome. The transition of leadership from Moses to Joshua presents a valuable model for contemporary Christian leaders to emulate in order to avoid this syndrome. This article aims to reflect on the text of Deuteronomy 31–34, which chronicles the concluding phase of Moses' leadership over the Israelites. Utilizing a literature study method, this research examines the text of Deuteronomy 31–34 through a thorough review of books, journal articles, and other relevant documents. The findings indicate that the narrative of Moses' leadership transition to Joshua offers practical guidance for preventing post-power syndrome. Key preventive measures include recognizing one's own limitations and adhering to divine directives, cultivating self-control and humility, prioritizing the welfare of others, and willingly transferring authority with prayer and a sincere blessing for the successor.